VD_FINDINFO Jug / 2016 / 210 vom 26. Mai 2015 - VD Tribunal cantonal (2015)
ENLÈVEMENTINFRACTION, LÉSION CORPORELLE, INSTIGATION, MENACEDROIT PÉNAL, DÉFAUTCONTUMACE | 123 ch. 1 CP, 123 ch. 2 al. 3 CP, 180 al. 2 let. a CP, 183 CP, 24 CP